The management of discipline and grievances in British workplaces: the evidence from 2011 WERS. Issue 1 (January 2017) - Wood, Stephen; Saundry, Richard; Latreille, Paul
Abstract: This study tests the assumptions and prescriptions of the Gibbons' Review of dispute resolution in the UK. Contrary to these, the formalisation of dispute resolution has continued and is not strongly related to the level of disputes or tribunal cases nor is the use of mediation which is complementing not replacing formalisation.